EFFECTIVENESS OF REARING EQUIPMENT ON THE SURVIVAL AND GROWTH OF PEARL OYSTER (Pinctada maxima) SEED AT KODEK BAY, NORTH LOMBOK - M S Hamzah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Oyster seeds mass mortality is one of the problemes in pearl farming business. Extreme temperature changes may cause mortality in oyster seed within sehll size of 3-4 cm. Modification in rearing equipment is therefore needed to maintain oyster survival from the impact of seasonal temperature fluctuation. The aim of this research was to observe the effectiveness and effect of rearing equipment on the survival and growth of pearl oyster (Pinctada maxima) seed at Kodek Bay, North Lombok. This research conducted from March- November 2009 was the continuation from the previous observation (December 2008-February 2009). Percentage of pearl oyster seed survival reared in “tento” basket was 84%, while that in pocket was 53%. “Chi-square” test showed that pearl oyster survival rate was siginifcantly affected by using the two equipment influence within 95% confidence level with ratio of 1.00:1.06. The growth of shell width, thickness, and weight of oyster seed tended to be higher reared in a“tento” basket (having broader space for movement) than that reared in a pocket. Length-weight relationship for those treatments showed similar pattern with minor allometry (b<3). Keywords: “Tento”basket, pocket, survival, growth, pearl oyster seed, Pinctada maxima